Gambaran Faktor-Faktor yang Mempengaruhi Kecemasan pada Pasien Diabetes Melitus - Noer Chariesmalillah; Erna Melastuti; Ahmad Ikhlasul Amal (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Several problems occur in patients with diabetes mellitus, one of which is anxiety. Anxiety is a vague feeling of worry and is usually related to worrying about unexpected dangers that occur in the future. Anxiety can increase blood cortisol levels and increase the risk of progressive insulin resistance, which can lead to increased blood sugar levels.The purpose of this study was to describe the factors that influence anxiety in patients with diabetes mellitus.The type of research taken in this study is descriptive research, which is to see a description of the phenomena that occur in a certain population with a cross sectional data collection level. Data collection with AIS, DSES, HDFSS questionnaires with 114 respondents at RSI Sultan Agung Semarang with purposive sampling technique and data analysis using univariate analysis. Of the 114 respondents, the research results showed that the age of 51-60 was 45 people (39.5%), female gender was 75 people (65.8%), Muslim religion totaling 114 people (100%), long suffering from DM 1-5 years as many as 79 people (69.3%), did not have complications as many as 62 people (54.4%), low education (Not in School, Elementary School, Junior High School) as many as 79 people (69.3%), self-employed work as many as 57 people (50%), and income> Rp. 2. 500-000 - Rp 3,500.00 / month as many as 35 people (30.7%), moderate self-acceptance as many as 67 people (58.8%), good spirituality level as many as 86 people (75.4%), and high family support as many as 83 people (72.8%). The results of this study show that the factors that influence the anxiety of patients with diabetes mellitus are age, gender, religion, duration of DM, complications, education, occupation, income, self-acceptance, level of spirituality, family support.